Water supply management (case study of Asajaya District) - Kirupaliny Susiee, Bhaskaran (University Malaysia Sarawak, UNIMAS, 2015)
This research project was focused on the water resource management in Asajaya which is located in the Samarahan division, a district in Sarawak. It has been known for frequent water shortage during dry season. Thus, this study is conducted to identify the cause of frequent water shortage in that area and to propose possible correction measure based on current water resource management. Data collection was done by gaining non classified data and conducting oral interview with the management authority. A questionnaire is designed to be administered to the residents of Asajaya. It is figured that water shortage occurs because water consumption exceeds water production. During dry season, insufficient raw water intake is available to meet the demands of because of population growth. Insufficient amount of funding required by Asajaya dissolved air flotation (DAF) water treatment plant results in low capacity of treatment facilities and maintenance. It is suggested that alternative site for raw water intake should be proposed to overcome the problem besides from implementing Integrated Water Resource Management (IWRM) principle.